Benefício social da política de crédito rural destinada à avicultura de corte no Brasil no período de janeiro de 1997 a dezembro de 2004 - Neves, Valéria Avinte de Almeida e (2007)
In this research, the social impact of the rural credit policy addressed to the Brazililan cut-up chicken raising between January 1997 and December 2004 was evaluated. This evaluation consisted on the social benefit analysis through the changing at the structure of the chicken meat. The used model was developd by Linder & Jarret, modified by Rose, taking into consideration the parallel and pivotal displacement to the offer curve. For methodology application, the minimal square method was used in two stages, with the simultaneous equations model approach. The results showed that the chicken meat offer in Brazil is elastic and the rural credit policy addressed to the Brazilian chicken raising generated a total benefit of R$ 186.926.769,54, taking into consideration a parallel displacement of the curve, in other words, an offer ampliation with production costs reduction. However, when taking into consideration the constant average cost, pivotal displacement of the offer curve, the total benefit generated by the rural credit policy results a total of R$ 102.135.880,94. This represents 83% difference in benefits, which reveals the importance of attitude turned to production cost reduction as a way to stimulate the aviculture development in the country.